2022
DOI: 10.46886/ijarppg/v8-i1/7412
|View full text |Cite
|
Sign up to set email alerts
|

Kenya-China Cooperation and Implementation Actors Amidst Policy Transfer and Learning Processes

Abstract: Amidst the policy transfer and learning processes in China-Africa relations, pertinent influences have arisen: dimensions of involvement, involved actors and process localization, especially regarding the youth. The presented insights highlight context and dynamics in the Kenya-China cooperation and implementation actors amidst policy transfer and learning processes. Integrative literature review methodology was adopted. Though Kenya-China relations involve state and non-state actors, the Forum on China-Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Although it was beyond the scope of this study to determine the enforcement and implementation of the different institutional alcohol and drug abuse policies, this could most probably vary and significantly affect or contribute to the differences observed in the odds of lifetime substance use among the colleges. Elsewhere, Otieno et al in a 2015 thesis [ 35 ] on implementation of alcohol and drug abuse policy in Kenyan universities found that there was lack of resources, training and even screening tools needed to implement policy. The study [ 35 ] adopted the Contextual Interaction Theory (CIT) of policy implementation which states that for policy to be successful, resources, training, and clear patterns of communication between actors must be available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it was beyond the scope of this study to determine the enforcement and implementation of the different institutional alcohol and drug abuse policies, this could most probably vary and significantly affect or contribute to the differences observed in the odds of lifetime substance use among the colleges. Elsewhere, Otieno et al in a 2015 thesis [ 35 ] on implementation of alcohol and drug abuse policy in Kenyan universities found that there was lack of resources, training and even screening tools needed to implement policy. The study [ 35 ] adopted the Contextual Interaction Theory (CIT) of policy implementation which states that for policy to be successful, resources, training, and clear patterns of communication between actors must be available.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, Otieno et al in a 2015 thesis [ 35 ] on implementation of alcohol and drug abuse policy in Kenyan universities found that there was lack of resources, training and even screening tools needed to implement policy. The study [ 35 ] adopted the Contextual Interaction Theory (CIT) of policy implementation which states that for policy to be successful, resources, training, and clear patterns of communication between actors must be available. Hence resources are clearly needed for implementation; yet in Kenya only 0.01% of the National Health budget is allocated to Mental Health [ 36 ].…”
Section: Discussionmentioning
confidence: 99%